Digital Language of Atomic Weights of the Chemical Elements - Kurić, Lutvo (International letters of chemistry, physics and astronomy, 2014)
The subject of this thesis is a digital approach to the investigation of the digital basis of digital Periodic Table – periods 4 and 5. A period 4 element is one of the chemical elements in the fourth row (or period) of the periodic table of the elements. The fourth period contains 18 elements, beginning with potassium and ending with krypton. As a rule, period 4 elements fill their 4s shells first, then their 3d and 4p shells, in that order, however there are exceptions, such as chromium. A period 5 element is one of the chemical elements in the fifth row (or period) of the periodic table of the elements. The fifth period contains 18 elements, beginning with rubidium and ending with xenon. As a rule, period 5 elements fill their 5s shells first, then their 4d, and 5p shells, in that order, however there are exceptions, such as rhodium. The digital mechanism of those periods have been analyzed by the application of cybernetic methods, information theory and system theory, respectively. This paper is to report that we discovered new methods for development of the new technologies in chemistry. It is about the most advanced digital technology which is based on program, cybernetics and informational systems and laws. The results in practical application of the new technology could be useful in chemistry, bioinformatics, genetics, bio-chemistry and other natural sciences.